Percentage of Body Fat versus Body Mass Index in Diagnosing Obesity - Mousa, Ali Abdulhussein; Mohammed, Salam Jasim; Kareem, Bashar Raouf (Medical Science Journal for Advance Research, 2025)
Background: Body mass index (BMI) is a common method for diagnosing obesity, however, whether its results regarding excess adiposity is correct remains debatable. Bioelectrical impedance analysis (BIA) gives a direct estimation of body fat percentage (BF%) which may more accurately represent obesity prevalence. Objective: To assess the diagnostic accuracy of BMI in identifying obesity in comparison with BF% assessed through BIA in a sample of Iraqi adults. Methods: A cross-sectional study was completed with 200 adults (100 males, 100 females) aged 18-60, recruited from the Nutrition Clinic at Al-Sader Medical City in Al-Najaf, Iraq. Anthropometrics were taken, and BF% was measured using an InBody 370 BIA machine. Obesity was classified as BF% > 28% for females and > 20% for males. BMI were classified using the ≥30 kg/m² and ≥25 kg/m² cut-offs to test the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Results: At BMI ≥30 kg/m², obesity prevalence was 30% in males and 36% in females. In comparison to BF% measured obesity, prevalence was higher at 56% in males and 58% in females. Both males and females aged over 30 and overweight by a scale of 30kg/m2 were recorded to have a high degree of specificity (100%) but a low degree of sensitivity (53.6% in males and 62.1% in females). When the criteria were changed to a BMI of 25 kg/m2, there was an increase in overall sensitivity to 84.2% with little loss of specificity (95.3%). Conclusion: Muscle and fat mass are generally differentiated with little precision when the BMI is in the middle range. Although there is a positive correlation between BMI and BF %, the classification of non-obese people with excess body fat as non-obese is significant. BMI is still a useful tool to gauge the extent of obesity in a population, but there have to be better methods to support the recorded figures.